Reviews (Modern theology, 1996)
Book reviewed in this article: Systematic Theology Volume2by wolfhart Pannenberg, translated by Geoffrey W. Bromiley The Church and the Churches: Toward an Ecumenical Ecclesiology by G. R. Evans The Royal Priesthood: Essays Ecclesiological and Ecumenical by John Howard Yoder The Promise of Pragmatism: Modernism and the Crisis of Knowledge and Authority by John Patrick Diggins Barth, Derrida and the Language of Theology by Graham Ward